Crossrail Project : infrastructure design and construction. Volume 4 - Williams, Rhys Vaughan; Black, Mike (Engineering geologist) (ICE Publishing, 2018)
This work contains a collection of 23 papers submitted to Crossrail's Technical Papers Competition. Contributions have come from consultants, contractors, suppliers and third-party stakeholders all of whom have been involved in the Crossrail project. The papers cover a variety of disciplines including health and safety, insulation materials, material corrosion, ground engineering and many more.